Peran Guru Bimbingan Konseling dalam Meningkatkan Kepercayaan Diri Siswa SD di Kelurahan Brandan Timur Baru - Ali Daud Hasibuan; Danil Dalimunthe; May Syaroh Harahap; Muhammad Fiqri Ramadhan; Sri Intan Siregar (Journal on Education, 2024)
The background of this research is the variation in students' Brandan Timur Baru and the various ways counseling teachers deal with students' problems at school. The research objectives are 1) to describe the state of student self-confidence. 2) Analyze the factors that cause students' self-doubt. 3) Describe the role of the counseling teacher in increasing students' self- confidence. The type of research used is qualitative research with a descriptive approach. Data analysis techniques are data reduction, data display, and conclusions. The research informants were school principals, vice principals for student affairs, counseling teachers, homeroom teachers, subject teachers, and students. The results of the study, 1) The condition of students' self- confidence tends to be low, namely not daring to express opinions, not daring to ask questions when they don't understand the lesson, hesitant when speaking in front of the class and silent when appointed by the teacher to come to the front of the class. 2) The factors that cause students' self- doubt are not daring to express opinions and ask questions because they feel embarrassed, afraid of giving wrong answers, and the nature of students is quiet who doesn't like to talk a lot. 3) The role of the Counseling teacher in increasing student self-confidence begins with designing the Counseling Guidance service program, classifying each student case, and providing information on how to increase student self-confidence. The conclusion of the study, Counseling teachers play an important role in increasing students' self-confidence. Suggestion 1) Schools should maximize the performance of the guidance counselor by scheduling them to attend class every week on a scheduled basis for at least 2 hours of lessons. 2) Counseling teachers should take an approach through various types of services and support activities for students who lack self-confidence so that they can get to know students better and can guide students to be more confident. 3) Students should be more courageous to speak/ask questions in class, not to be afraid of making mistakes in learning and to take advantage of counseling services in schools so that they are more confident.